Sharpening of periodontal instruments with different sharpening stones and its influence upon root debridement--scanning electronic microscopy assessment - Silva, Marcelo Vieira; Gomes, Débora Aline Silva; Leite, Fábio Renato Manzolli; Sampaio, José Eduardo Cezar [UNESP]; de Toledo, Benedicto Egbert Correia; Mendes, Ary José Dias (My University, 2006)
The objective of this study was to evaluate, through scanning electronic microscopy, the effect of sharpening with different sharpening stones on the cutting angle of periodontal curettes (Gracey 5-6), and the influence on root surfaces after debridement and planing. The experimental model consisted of two different phases. In the first, the cutting angles of fifteen stainless steel Gracey 5-6 curettes were analyzed under a scanning electronic microscope after being sharpened with different types of stones. In the second phase, the root surfaces of 25 newly extracted teeth were evaluated with a scanning electronic microscope after being debrided with curettes sharpened with different stones. Analysis of the results showed that the synthetic stones (aluminum oxide and carborundum) are more abrasive and produce more irregular cutting angles, whereas Arkansas stones are less abrasive and produce smoother and more defined cutting angles. There was no significant statistical differences among the five groups tested with regard to the degree of irregularity of the root surfaces after instrumentation.
Keywords: aluminum oxide; dental alloy; inorganic compound; silicon carbide; silicon derivative; stainless steel; chemistry; human; instrumentation; methodology; periodontics; preventive dentistry; scanning electron microscopy; single blind procedure; surface property; tooth root; ultrastructure; Aluminum Oxide; Carbon Compounds, Inorganic; Dental Alloys; Humans; Microscopy, Electron, Scanning; Root Planing; Silicon Compounds; Single-Blind Method; Stainless Steel; Subgingival Curettage; Surface Properties; Tooth Root